A molecular phylogeny of carcinoecium-forming Epizoanthus (Hexacorallia: Zoantharia) from the Western Pacific Ocean with descriptions of three new species. Issue 8 (17th November 2019) - Kise, Hiroki; Montenegro, Javier; Ekins, Merrick; Moritaki, Takeya; Reimer, James Davis
Abstract : Many cnidarians have been reported in association with hermit crabs from shallow waters to the deep sea. Some of these actiniarians and zoantharians produce a carcinoecium, a chitin-like pseudo-shell. Many studies have been conducted on hermit crab–actiniarian symbioses, while hermit crab–zoantharian symbioses have received less attention due to the difficulty of specimen collection as they are exclusively found in the deep sea. In this study, 11 carcinoecium-forming specimens associated with hermit crabs of several genera were collected from the western Pacific Ocean. We formally described the collected specimens as Epizoanthus xenomorphoideus sp. nov., E. australis sp. nov., and E. gorgonus sp. nov. based on results of molecular phylogenetic analyses (COI, mt 12S-rDNA, mt 16S-rDNA, 18S-rDNA, ITS-rDNA) and morphological observations. Our phylogenetic results showed that there are two different subclades within a carcinoecium clade, and these subclades have different external morphologies. Further studies with more taxon sampling will enable a more comprehensive evaluation of the evolution and phylogenetic relationships of carcinoecium-forming zoantharian species.